Do shippers' characteristics influence port choice criteria? Capturing heterogeneity by using latent class models. (February 2022) - Martínez-Moya, Julián; Feo-Valero, María
Abstract: This paper focuses on the study of Spanish ceramic tile exporters' port choice criteria, an industry that is characterized by a low unit value index. Thus, transport costs highly influence the competitiveness of their products in international markets, representing a relatively high percentage of the value of the shipment. It is therefore critical for this type of industry to have access to efficient door-to-door maritime chains. Determinants of port choice are analysed through a latent class model allowing to link class membership to specific characteristics of the shippers and their shipments such as the size of the company, the value of the shipment, the destination market and the frequency of shipments. The results obtained show differences in the valuation of the attributes frequency, delays and closing time depending on the type of destination market. While companies exporting to deep-sea markets value specially the attributes frequency and delays, those exporting to the regional corridor are the only ones where the closing time is statistically significant. Policies designed show that when there is a strong competition between two ports to attract cargo from an overlapped hinterland, the ultimate effectiveness of the measures would depend on its competitor's strategic movement and the measures implemented there. Highlights: The paper focuses on the study of port choice criteria from shippers' perspective An application to exporters belonging to Spanish ceramic tile industry We use latent class model to better capture heterogeneity in shippers' preferences Results show differences in attributes depending on the type of destination market. The specialization of the port in each type of traffic is a relative advantage